EVEKTIFITAS PENGEMBANGAN BAHAN AJAR BAHASA INDONESIA BERBASIS CIRC SISWA SEKOLAH DASAR SIMANGAMBAT - Weni Aulia; Sartika Rati Asmara Nasution (Jurnal Education and Development, 2020)
This research is motivated by the teaching materials used that do not attract students to read, educators still use conventional teaching materials, namely teaching materials that are used, just buy, instant, and without the effort of planning, preparing, and composing their own. Thus the risk is very likely that the teaching materials they use are unattractive, monotonous, and not in accordance with the needs of students. This causes teachers to be able to develop reading teaching materials in accordance with reading steps, one of which is by using the CIRC model. The purpose of developing this teaching material is to produce valid, practical, and effective teaching materials. This type of research is a 4-D model development research. Based on the validity test, the percentage of teaching materials was 88.56% (very valid). The results of the teacher response assessment test obtained a percentage of 87.49% (very practical) and student response assessments 87.81% (very practical) and the observation sheet on the use of teaching materials obtained a percentage of 94.6% (very valid). So it can be concluded that reading comprehension teaching materials based on the Cooperative Integrated Reading and Compotition (CIRC) model developed can be declared valid, practical, and effective